Impact of TP53 mutation status in elderly AML patients when adding all-trans retinoic acid or valproic acid to decitabine - Bresser, Helena; Schmoor, Claudia; Grishina, Olga; Pfeifer, Dietmar; Thomas, Johanna; Rehman, Usama-Ur; Crysandt, Martina; Jost, Edgar; Thol, Felicitas; Heuser, Michael; Götze, Katharina S.; Schlenk, Richard Friedrich; et al. (European journal of haematology, 2024)
In a randomized phase II trial (AMLSG 14-09, NCT00867672) of elderly, newly diagnosed AML patients, ATRA combined with decitabine (DEC) significantly improved the overall response rate (ORR) and survival also in patients with adverse-risk genetics, without adding toxicity. We performed a post hoc analysis to determine the predictive impact of TP53 status. Despite a nominally higher ORR, the clinically meaningful survival benefit when adding ATRA to DEC was diminished, but not completely negated, in TP53-mutated patients. Indeed, 2 out of 14 TP53-mutated patients (14%) randomized to a DEC + ATRA-containing regimen lived for > 36 months. Further studies of ATRA combined with hypomethylating agents appear warranted in non-M3 AML patients ineligible for HMA/venetoclax therapy.
Gesehen am 10.06.2025